Carbon and Nitrogen Surface Contamination Contributions in ZnO Nanowire Based Hydrogen Sensing - Aurelian Marcu; Sorin Vizireanu; Razvan Mihalcea; Veronica Satulu; Maria Balan; Marius Dumitru; Valentin Craciun; Catalin Constantin; Cristian Viespe (Chemosensors)
Hexagonal ZnO nanowires were grown using the PLD/VLS technique on a SAW sensor active area for hydrogen sensing. The influence of different carbon and nitrogen surface contaminant concentrations on sensor output was investigated for three active area cases: a few weeks’ exposure to free ambient air contamination, 3 h at 600 °C thermal desorption of carbon, and (room temperature) plasma-activated nitrogen and carbon contamination. Correlations between sensing performance and contamination element concentration were established. To understand the adsorption versus absorption mechanisms, similar studies were further performed on circular ZnO nanowires morphology, which have a different surface-area-to-volume ratio. Comparative results show that, while a 20% carbon surface contamination variation generates a variation of 3–5% in nanostructure hydrogen sorption, nitrogen surface contamination influence depends on nanostructure morphology. Thus, in our comparative studies, for the case of a nanowire hexagonal cross-section a 12% nitrogen surface contamination variation generates a 5–7% increase in hydrogen adsorption and also an increase of 6–8% in hydrogen absorption. Consequently, the catalytic effect of nitrogen could enlarge the linear response of nanowire-based (SAW) sensors over a wider hydrogen concentration range.